Hormonal and blood pressure changes during converting enzyme inhibition by teprotide. - VandenBurg, M. J. (BMJ Group, 1981)
Changes induced by i.v. and subcutaneous teprotide in plasma renin, angiotensin I, angiotensin II, aldosterone and bradykinin were studied in a renal transplant patient with severe high renin hypertension, before and after trinephrectomy. The immediate reduction in BP produced by teprotide was not solely attributable to the inhibition of conversion of angiotensin I to angiotensin II, because there was also a transient increase in serum bradykinin; however, the prolonged antihypertensive effect of teprotide appeared independent of bradykinin. After trinephrectomy, teprotide lowered systolic BP but had no significant effect on diastolic BP or plasma bradykinin. beta-Blockade prevented the secondary increase in plasma renin which followed teprotide, thereby potentiating its anti-hypertensive effect.